2007
DOI: 10.1002/mrd.20752
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic changes in localization of chromobox (CBX) family members during the maternal to embryonic transition

Abstract: The Chromobox domain (Cbx) gene family, consisting of Polycomb and Heterochromatin Protein 1 genes, is involved in transcriptional repression, cell cycle regulation and chromatin remodeling. We report the first study of gene expression and protein localization of the Cbx genes in in vitro produced bovine embryos. All but one gene (Cbx6) were expressed. This was confirmed by immunolocalization for HP1alpha, beta, gamma, and Pc2, 3. HP1beta was found in the nuclei of embryos from the two-cell stage onwards, wher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 39 publications
1
15
1
Order By: Relevance
“…However, certain points require further study. Firstly, dynamic localization of the nuclear-cytoplasmic and/or sub-nuclear distribution of members of the Cbx family occurs during the maternal-to-embryonic transition (42). The present study revealed that Cbx2 was predominantly expressed in the cytoplasm.…”
Section: Discussionmentioning
confidence: 99%
“…However, certain points require further study. Firstly, dynamic localization of the nuclear-cytoplasmic and/or sub-nuclear distribution of members of the Cbx family occurs during the maternal-to-embryonic transition (42). The present study revealed that Cbx2 was predominantly expressed in the cytoplasm.…”
Section: Discussionmentioning
confidence: 99%
“…Fluorescence in situ hybridisation probe generation and digoxigenin labelling A partial polymerase chain reaction (PCR) product (288 bp) of HP1g (Ruddock-D'Cruz et al 2008) was ligated into pGEM-T Easy plasmid and grown on agar according to the manufacturer's instructions (pGEM-T Easy Vector System; Promega). Clones containing the HP1g insert were cultured and cDNA produced from the whole plasmid by PCR.…”
Section: Confocal Microscopy and Image Manipulationmentioning
confidence: 99%
“…HP1a, HP1b and HP1g) share conserved N-terminal (chromodomain) and C-terminal (chromoshadow domain) domains, coupled by a less conserved hinge domain. Despite considerable primary sequence homology, mammalian HP1 variants differentially bind mono-and olignucleosomes and linker histones in vitro (Nielsen et al 2001) and can localise to euchromatic and/or heterochromatic regions (Minc et al 2000;De Lucia et al 2005;Ruddock-D'Cruz et al 2008). The localisation and activity of the HP1 protein is regulated by ubiquitous and isoform-specific acetylation, methylation, sumoylation and ubiquitination (Lomberk et al 2006).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations